Boron nitride nanotube mixture for producing boron nitride nanotubes
Patent Information
- Application Number
- JP2022195650
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-16
- Filing Date
- 2022-12-07
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-11-12
AI Technical Summary
【0010】 本発明は、窒化ホウ素フラーレンや窒化ホウ素薄片などの強化効果の小さい副生成物の割合を低減し、同時に収率を高められ、さらに熱酸化処理の必要ない窒化ホウ素ナノチューブの製造方法に用いられる窒化ホウ素ナノチューブ混合液を提供できる。
Smart Images

Figure 0007632439000001 
Figure 0007632439000002 
Figure 0007632439000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a boron nitride nanotube mixture. [Background technology]
[0002] For example, as described in Patent Document 1, boron nitride nanotubes are obtained by reacting a mixture of magnesium oxide, iron (II) oxide (FeO) and boron powder with ammonia gas at 1100 to 1700°C. The obtained boron nitride nanotubes are treated with nitric acid to remove the magnesium and iron used as catalysts. This method makes it possible to produce uniform boron nitride nanotubes with a diameter of 20 to 50 nm. It is disclosed that the obtained boron nitride nanotubes are added to an organic solvent solution in which a polymer, poly[m-phenylenevinylene-co-(2,5-dioctoxy-p-phenylenevinylene)], is dissolved in an organic solvent such as chloroform, and the boron nitride nanotubes are coated with the polymer, i.e., polymer wrapping is performed to obtain a uniform and transparent boron nitride nanotube dispersion liquid. Also disclosed is a purification method in which insoluble matter is removed by ultrasonic treatment and centrifugation at room temperature for 2 hours to produce a uniform, transparent dispersion, the organic solvent is evaporated from this dispersion, and PmPV is removed by pyrolysis to obtain boron nitride nanotubes with a uniform diameter. Note that in the following explanation, poly[m-phenylenevinylene-co-(2,5-dioctoxy-p-phenylenevinylene)] is abbreviated to PmPV.
[0003] Recently, as shown in Patent Document 2, it has become possible to continuously produce thin (diameter 10 nm or less), reasonably pure BNNTs in high yield at or near atmospheric pressure very efficiently without the need for metals as catalysts. Specifically, a method for producing boron nitride nanotubes (BNNTs) is disclosed, which includes providing one or more sources of boron, nitrogen, and hydrogen to a stable induction plasma at a plasma temperature in the range of 1,000-10,000 K to form a reaction mixture of boron, nitrogen, and hydrogen in the plasma under a pressure of more than 0.6 atm and less than 2 atm, and cooling the reaction mixture to form BNNTs, wherein the one or more boron sources include elemental boron, boron nitride, borane, ammonia borane, borazine, or any mixture thereof.
[0004] Using this, Patent Document 3 discloses a boron nitride nanotube material that includes boron nitride nanotubes and boron nitride fullerene hollow particles, the boron nitride fullerene hollow particles being dispersed among the boron nitride nanotubes, and the boron nitride fullerene hollow particles being in contact with and interposed between the boron nitride nanotubes. This discloses a method in which, for example, in the boron nitride nanotubes obtained in Patent Document 2, etc., boron is converted to boron oxide (B2O3) by oxidation heat treatment, and then the boron oxide is washed and removed with ethanol, methanol, water, etc. in which boron oxide dissolves. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-230830 A [Patent Document 2] Special Publication No. 2016-521240 [Patent Document 3] International Publication No. 2020 / 031883 Summary of the Invention [Problem to be solved by the invention]
[0006] The problem with the products synthesized by the manufacturing methods of Patent Document 1 and Patent Document 2 is that they contain a high proportion of by-products such as boron nitride fullerenes and boron nitride flakes, which have a smaller aspect ratio than boron nitride nanotubes and have a small reinforcing effect when composited with metals, ceramics, etc. Boron nitride nanotubes and by-products such as boron nitride fullerenes and boron nitride flakes have similar crystal structures and are easily generated during the synthesis process. Therefore, Patent Document 1 discloses a purification method for reducing the proportion of these by-products, but the yield of boron nitride nanotubes is reduced. Furthermore, the dispersibility of boron nitride nanotubes is reduced due to adhesion between the boron nitride nanotubes and by-products by the thermal oxidation treatment described in Patent Document 2 and Patent Document 3.
[0007] The object of the present invention is to provide a boron nitride nanotube mixture for use in a method for producing boron nitride nanotubes that can reduce the proportion of by-products such as boron nitride fullerenes and boron nitride flakes that have little reinforcing effect, while at the same time increasing the yield, and does not require a thermal oxidation treatment. [Means for solving the problem]
[0008] The present invention relates to a method for producing a polymerizable composition comprising a boron nitride nanotube, a nonionic polymer having a CH group with sp3 bonding, and an organic solvent. and containing boron nitride fullerenes or boron nitride flakes Characterized by For producing boron nitride nanotubes This is a boron nitride nanotube mixture.
[0009] Preferably, the polymer dispersant contains ethyl cellulose or polyvinyl butyral. Preferably, the organic solvent is benzyl alcohol. Preferably, the surface of the boron nitride nanotube is covered with an amorphous material. Preferably, the raw material containing the boron nitride nanotube is mixed with 1 part by mass of a nonionic polymer dispersant having a CH group with sp3 bonding, and 200 to 100,000 parts by mass of the organic solvent. Effect of the Invention
[0010] The present invention can provide a boron nitride nanotube mixture that can be used in a method for producing boron nitride nanotubes that reduces the proportion of by-products such as boron nitride fullerenes and boron nitride flakes that have little reinforcing effect, while at the same time increasing the yield, and does not require thermal oxidation treatment. [Brief description of the drawings]
[0011] [Figure 1] Low magnification TEM image of the recovered BNNT product. [Diagram 2] 1 is a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion liquid of Example 1. [Diagram 3] 1 is a high-resolution TEM image of a sample obtained by removing the solvent from the BNNT dispersion liquid of Example 1. [Figure 4] 4 is a high-resolution TEM image of a sample obtained by drying the BNNT dispersion liquid of Example 1 and then heat-treating it in air at 500° C. for 1 hour. [Diagram 5] 13 is a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion liquid of Example 2. [Figure 6] 1 is a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion liquid of Comparative Example 1. [Figure 7] 13 is a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion liquid of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, a method for producing boron nitride nanotubes according to an embodiment of the present invention will be described with reference to the drawings. In the following description, boron nitride nanotubes may be abbreviated as BNNTs.
[0013] First, the process of mixing the synthesis product from which moisture has been removed, i.e., the raw material containing boron nitride nanotubes, a nonionic polymer dispersant having sp3 bonding CH groups, and an organic solvent to obtain a suspension will be described. Among these, dissolving the nonionic polymer dispersant having sp3 bonding CH groups in an organic solvent to prepare a uniform solution in advance is preferable in order to uniformly coat the boron nitride nanotubes with the polymer dispersant. The synthesis product is added to this solution, and ultrasonically dispersed by a homogenizer or the like, so that the boron nitride nanotubes are uniformly coated with the polymer dispersant. It is preferable to perform the process while cooling in order to prevent the liquid temperature from increasing during ultrasonic dispersion. In the present invention, the "product after synthesis" does not only refer to a product immediately after synthesis, but also includes a product that has been subjected to other treatments after the synthesis of BNNTs and prior to the process according to the present invention. In other words, the raw material containing boron nitride nanotubes is not limited to the product as synthesized, but also includes a boron nitride nanotube product in which by-products contained in the product as synthesized have been removed to a certain extent by other treatments or the like. Therefore, in the following description, the "product after synthesis" is intended to include all raw materials containing boron nitride nanotubes used in the manufacturing process of BNNTs according to the present invention described below.
[0014] As the nonionic polymer dispersant having sp3-bonding CH groups, it is preferable to use cellulose-based polymers such as ethyl cellulose, methyl cellulose, propyl cellulose, butyl cellulose, hydroxypropyl cellulose, and acetyl cellulose, which are polymers having a substituted glucose structure in which at least one of the hydroxyl groups at the 2nd, 3rd, and 6th positions is an alkyl ether, and linked at the 1st and 4th positions, or vinyl-based polymers having at least one or more methylene groups and at least one or more substituted methylene groups in the repeating unit, such as polyvinyl butyral, polyvinyl formal, polyvinyl acetate, ethylene-vinyl acetate polymer, polystyrene, polyvinyl alcohol, polyacrylonitrile, polyvinyl methyl ketone, and polymethyl methacrylate. This is because the symmetry of the π orbital of boron nitride nanotubes is low, and polymers that have CH / π interactions with boron nitride nanotubes are more likely to bond to boron nitride nanotubes than polymers that have π / π interactions with boron nitride nanotubes, such as the polymer applied in Patent Document 1. In addition, the main chain of the nonionic polymer having sp3 bonding CH groups is more flexible than the sp2 bonding main chain of the polymer used in Patent Document 1, and therefore more likely to wind around small boron nitride nanotubes. For this reason, it is believed that the small boron nitride nanotubes obtained in Patent Documents 2 and 3 in particular can be more easily coated by using a nonionic polymer dispersant having sp3 bonding CH groups. Carboxymethylcellulose (CMC), which is widely used as a polymer dispersant for carbon nanotubes (CNTs), is an ionic polymer with sp3-bonding CH groups, and is used in aqueous solvents. When this CMC is used as a dispersant for small-diameter BNNTs, micelles are formed around the BNNTs, and the BNNTs are solubilized by being encapsulated in the hydrophobic space formed by the micelles. However, the size of the micelles follows the shape of the substance, so that the substance is solubilized regardless of its shape, and by-products other than BNNTs are also solubilized. For this reason, it is thought that CMC has difficulty selectively solubilizing only small-diameter BNNTs. On the other hand, in the case of nonionic polymers with sp3-bonding CH groups, micelles are not formed around the BNNTs because an organic solvent is used. For this reason, differences in the shapes and sizes of BNNTs and impurities (by-products other than BNNTs) cause differences in the adsorption and solubilization properties of the dispersant to each of them, making it easier to separate BNNTs and impurities, and selectively dispersing BNNTs.
[0015] Examples of the organic solvent that can be used include benzyl alcohol, methanol, ethanol, isopropyl alcohol, butanol, acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, ethyl acetate, butyl acetate, N-methylpyrrolidone, N-dimethylformamide, cyclohexanone, isophorone, tetrahydrofuran, 2-methyltetrahydrofuran, ethyl lactate, butyl lactate, and ethylene glycol dimethyl ether.
[0016] After mixing the raw material, the dispersant, and the organic solvent, the mixture may be stirred, for example, with an ultrasonic homogenizer. The stirring conditions are set according to the separation property of the by-products and the effect of preventing the destruction of the BNNTs, by performing a separation process described later after stirring under predetermined stirring conditions, and checking SEM images of the supernatant and the residue. For example, stirring is performed under a plurality of conditions, and the amount of by-products is relatively small in the supernatant from each image after separation, and conditions are set under which the destruction and breakage of the BNNTs are not noticeable, or the amount of broken BNNTs in the residue is not noticeable. For example, a frequency of 20 kHz, an ultrasonic amplitude of 40 to 80 μm, and a stirring time of about 20 to 40 minutes are preferable, and the boron nitride nanotubes are not easily destroyed and are easily dispersed. A suspension is obtained by the above operations.
[0017] The composition of the suspension obtained by mixing the product after synthesis, that is, the raw material containing boron nitride nanotubes, the nonionic polymer dispersant having sp3 bonding CH groups, and the organic solvent, may be, for example, 1 part by mass of the raw material containing boron nitride nanotubes, 1 to 2000 parts by mass of the nonionic polymer dispersant having sp3 bonding CH groups, and 200 to 100,000 parts by mass of the organic solvent. The lower limit of the amount of the dispersant added is set according to the separability of the by-products, for example, by performing a separation step described later and checking SEM images of the supernatant and residue. For example, the amount of the dispersant added is changed under multiple conditions, and the conditions are set under which the amount of BNNTs in the supernatant is relatively large and the BNNTs are not bundled, or the amount of BNNTs in the residue is not noticeable, based on each image after separation. The upper limit of the amount of dispersant added is set, for example, by checking the light absorption characteristics in the ultraviolet region of the dispersion liquid after the separation step described below, and based on the relationship between the maximum absorption and the amount added, under conditions where the increase in the amount of light absorption is approximately saturated as the amount added increases. In this way, with respect to the range of dispersant and solvent, it is preferable for the amount to be equal to or less than the upper limit since it is economical and there is no waste, and it is preferable for the amount to be equal to or more than the lower limit since it improves the dispersibility of the BNNTs. The presence or absence of bundling of BNNTs can be determined, for example, by looking at SEM images or the like, if the BNNTs after dispersion are thicker than the BNNTs in the raw material, it is determined that several to several tens of BNNTs have been bundled during dispersion.
[0018] Next, the process of centrifuging the obtained suspension will be described. By this operation, by-products are removed. Here, the by-products refer to BN fullerenes and h-BN flakes with boron particles as their cores contained in the above solution. The conditions of the centrifugation to separate these by-products are set according to the separability of the by-products by checking the SEM images of the supernatant and residue after the separation process. For example, by changing multiple conditions (time, centrifugal force), the conditions are set so that the amount of by-products in the supernatant is relatively small and the amount of dispersant polymer (a film-like substance that entirely covers the by-products) in the residue is relatively large from each image after separation. For example, the centrifugal acceleration may be set to 30,000 G or more, the processing time may be 1 hour or more, and the liquid temperature may be set to 25°C.
[0019] Finally, the process of centrifuging the obtained suspension, removing the by-products contained in the raw materials, and obtaining a dispersion containing boron nitride nanotubes will be described. The by-products can be removed from the suspension using, for example, a high-speed refrigerated centrifuge. By removing the by-products contained in the raw materials, a BNNT dispersion can be obtained in which BNNTs coated with a nonionic polymer having sp3-bonding CH groups are dispersed in an organic solvent.
[0020] Furthermore, a method for obtaining BNNTs from a BNNT dispersion will be described. First, the organic solvent is evaporated from the BNNT dispersion. In this process, the BNNTs are covered with a solid polymer dispersant. Next, the BNNTs covered with the dispersant are heated in the atmosphere at a temperature of 300°C to 900°C, thereby thermally decomposing and removing the dispersant. This allows the BNNTs contained in the dispersion to be purified to a high purity. A temperature of 300°C or higher is preferable because the dispersant is easily thermally decomposed. On the other hand, a temperature of 900°C or lower is preferable because the BNNTs can remain without being burned and lost, and a temperature of less than 650°C is preferable because it is lower than the temperature of the thermal oxidation treatment of boron particles, and therefore adhesion between the boron nitride nanotubes and by-products is avoided and the boron nitride nanotubes are easily dispersed.
[0021] Example 1 Next, an embodiment will be described. First, the boron nitride nanotube dispersion to be used for evaluation was prepared in the following manner. First, a small plasma device (TEKNA Plasma Systems Inc. TekNanо-15) was used to synthesize the BNNT product containing by-products, i.e., the raw material containing boron nitride nanotubes, as follows. First, the inside of the reaction vessel was purged with argon gas. Next, argon gas (flow rate: 10 L / min) was flowed in the central region, and a mixture of argon (30 L / min) and hydrogen (2.5 L / min) was flowed to flow a sheath gas around the outer periphery of the tube that confines the plasma. Nitrogen gas was flowed through both the torch nozzle (10 L / min) and the porous wall (47 L / min) surrounding the reaction vessel. A few minutes after the plasma ignition, when the temperature of the thermocouple installed between the reaction vessel and the cyclone became constant, the raw material h-BN powder (average particle size: 5 μm) was continuously fed from the feeder installed on the top of the plasma torch using argon (2.5 L / min) as carrier gas. The feed rate was 0.5 g / min, the operation time was 2 hours, and the pressure in the reaction chamber was 1 atm. After the synthesis was completed, the apparatus was disassembled and the products attached to the plasma torch, reactor, cyclone, and filter were collected.
[0022] The collected product after synthesis was observed under a microscope. Figure 1 shows a low-magnification transmission electron microscope (TEM) image of the product obtained. The product has BNNTs 101, BN fullerenes 102, and h-BN flakes 103. BN fullerenes 102 are substances that have a graphene structure in which B atoms and N atoms are alternately bonded, and have a spherical or spheroidal closed structure. The h-BN flakes 103 are sheet-like substances made of crystalline h-BN. Note that boron particles (black contrast areas) are incorporated in the BN fullerenes 102. Note that other synthesis methods may be used to synthesize the product.
[0023] Next, the synthesized product was used for each treatment according to the following method as Example 1. 25 mg of ethyl cellulose (EC) manufactured by Tokyo Chemical Industry Co., Ltd. was used as a dispersant, and 20 cm of benzyl alcohol was used as an organic solvent. 3 After mixing, 15 mg of the product synthesized above was added to this solution. That is, for 1 part by mass of the product after synthesis, i.e., the raw material containing boron nitride nanotubes, 1.7 parts by mass of the nonionic polymer dispersant having sp3 bond CH groups and 1333 parts by mass of the organic solvent were used. This mixture was dispersed for 20 minutes at room temperature using an ultrasonic homogenizer. Subsequently, the mixture was centrifuged for 3 hours at a centrifugal acceleration of 30,000G to remove by-products contained in the raw material, and a BNNT dispersion was obtained.
[0024] Figure 2 is a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion. It was confirmed that the BN fullerenes and h-BN flakes contained in the product after synthesis shown in Figure 1 had been removed. This indicates that the proportion of by-products with little reinforcing effect, such as boron nitride fullerenes and h-BN flakes, has been reduced.
[0025] Figure 3 is a high-resolution TEM image of the sample in Figure 2. The surface of the BNNT 301 was covered with an amorphous material 302 that was thought to be ethyl cellulose.
[0026] Next, in order to thermally decompose and remove the ethyl cellulose adhering to the BNNT surface, the BNNT dispersion was dried and then heat-treated in air at 500°C for 1 hour. In Patent Document 2, a step of air oxidation at a temperature in the range of 650°C to 850°C is required as the thermal oxidation treatment, but in Example 1, this step was not performed.
[0027] Figure 4 shows a high-resolution TEM image of a sample prepared by adding BNNTs that had been heat-treated in air to isopropyl alcohol, and then dropping the ultrasonically treated BNNT dispersion onto a copper grid covered with a carbon film. The amorphous layer on the BNNT surface had disappeared, and the sidewalls of BNNT401 were clearly observed, confirming that the BNNTs maintained a completely crystalline state.
[0028] Example 2 In Example 2, BNNTs were obtained in the same manner as in Example 1, except that the dispersant was polyvinyl butyral (PVB), a vinyl polymer. Figure 5 is a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion. As in Example 1, it was found that the proportion of by-products with little reinforcing effect, such as boron nitride fullerenes and h-BN flakes, was reduced.
[0029] Comparative Example 1 In Comparative Example 1, BNNTs were obtained in the same manner as in Example 1, except that the dispersant was poly[m-phenylenevinylene-co-(2,5-dioctoxy-p-phenylenevinylene)] (PmPV), a nonionic polymer having sp2-bonded CH groups. Figure 6 shows a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion. It was found that the proportion of by-products with little reinforcing effect, such as boron nitride fullerene and h-BN flakes, was reduced.
[0030] Comparative Example 2 In Comparative Example 2, BNNTs were obtained in the same manner as in Example 1, except that the dispersant was CMC (carboxymethyl cellulose), an ionic polymer having sp3-bonded CH groups, and water was used as the solvent. Figure 7 is a low-magnification TEM image of a sample obtained by removing the solvent from the BNNT dispersion. It was found that a large amount of by-products with little reinforcing effect, such as boron nitride fullerenes and h-BN flakes, remained.
[0031] In Example 1, Example 2, Comparative Example 1, and Comparative Example 2, it was found from the TEM images of the samples in which the solvent was removed from the BNNT dispersion that the amount of remaining by-products (BN fullerenes and h-BN flakes) was generally the smallest in Example 2, followed by Example 1 and Comparative Example 1, and the largest in Comparative Example 2. This is thought to be because the dispersant in Comparative Example 2 was an ionic polymer, and water was used as the solvent, so that micelles were generated around the BNNTs as described above, and the relatively coarse by-products (BN fullerenes and h-BN flakes) were also solubilized in the same way as the BNNTs, resulting in poor selective dispersibility of the BNNTs. Moreover, for each of Example 1, Example 2, Comparative Example 1, and Comparative Example 2, the yield of dispersed BNNTs was calculated by the following formula. Yield (%) = {([mass of product after synthesis] - [mass of residue after centrifugation]) / [mass of product after synthesis]} x 100 As a result, it was found that the yield was highest in the following order: Example 1 (55%)>Example 2 (51%)>Comparative Example 1 (32%)>Comparative Example 2 (20%). The dispersion of Comparative Example 1 has an sp2 bonding main chain, and therefore is more rigid than EC and PVB, which have sp3 bonding main chains, and is therefore less likely to wrap around thin BNNTs, resulting in poor dispersibility. These results show that when the dispersant of the present invention is used, the amount of remaining by-products is smaller (the purity of BNNTs is higher) and the yield of BNNTs is higher than when the dispersant of the comparative example is used.
[0032] The present invention is not limited to these examples, and various modifications are possible within the scope of the invention described in the claims, and it goes without saying that these modifications are also included in the scope of the present invention. For example, the conditions of ultrasonic waves and centrifugation used in producing the dispersion may be appropriately selected depending on the mass mixing ratio of the BNNTs, dispersant, and solvent. [Explanation of symbols]
[0033] 101, 301, 401...BNNT 102···BN fullerene 103...h-BN thin section 302 Ethyl cellulose
Claims
1. boron nitride nanotubes; a nonionic polymer having sp3-bonding CH groups; An organic solvent; having A boron nitride nanotube mixture for producing boron nitride nanotubes, comprising boron nitride fullerenes or boron nitride flakes.
2. 2. The boron nitride nanotube mixture for producing boron nitride nanotubes according to claim 1, wherein the non-ionic polymer comprises ethyl cellulose or polyvinyl butyral.
3. 2. The boron nitride nanotube mixture for producing boron nitride nanotubes according to claim 1, wherein the organic solvent is benzyl alcohol.
4. 2. The boron nitride nanotube mixture for producing boron nitride nanotubes according to claim 1, wherein the surfaces of the boron nitride nanotubes are covered with an amorphous material.
5. 2. The boron nitride nanotube mixture for producing boron nitride nanotubes according to claim 1, characterized in that it comprises a mixture of 1 part by mass of a raw material containing boron nitride nanotubes, 1 to 2,000 parts by mass of a nonionic polymer dispersant having an sp3-bonding CH group, and 200 to 100,000 parts by mass of the organic solvent.
Citation Information
Patent Citations
Boron nitride nanotube dispersion and method for producing the same, and method for refining boron nitride nanotube
JP2007230830A
Boron nitride nanotubes and method for producing the same
JP2016521240A
Method for purifying boron nitride nanotubes
JP2020514230A
Boron nitride nanotube material, boron nitride nanotube composite material, and method for producing boron nitride nanotube material
WO2020031883A1